Repensando el Estado como institución. Poder central, cultura local y relaciones centro-periferia en las interpretaciones de Juan Maiguashca y el debate Schwarz- Carvalho Franco - Cabrera Hanna, Santiago (2016)
This article aims to challenge the models of analysis about the nineteenthcentury state and its implications to the national formation, starting from a bibliographical review on some of the most relevant works about the theme, which is tackled here by taking into consideration the Ecuadorian and Brazilian cases. The reasons for doing so is to submit to close scrutiny one of the major historiographical interpretations of the process of national formation in Equator, which has turned out to be an important framework to Ecuadorian historiography about the subject. We refer to the study of the state as an institution, developed in the 1990s by Juan Maiguashca. The interpretive contributions of this scholar raised, at that time, challenging scenarios for a topic that until then had been defined by the view of the state as a structure of domination. This article retrieves critically this contribution by submitting to questioning the conception of central power formation, based on a center-periphery model of analysis present by the brazilian scholars Roberto Schwarz and Maria Sylvia de Carvalho Franco.